EFEKTIVITAS INTERVENSI STRES AKADEMIK SECARA DARING PADA SISWA KELAS 2 SEKOLAH MENENGAH ATAS - Safira Naila; Luh Surini Yulia Savitri (Akademika : Jurnal Teknologi Pendidikan, 2023)
Academic stress is one of the biggest stressors for adolescents. Facing academic stress, coping strategies being used is so important for deciding the impact of academic stress itself. This study aims to test the effectiveness of online intervention for enhancing coping stress strategies for lowering academic stress in students. Participants in this study were 2nd grade high school students (n=6) aged 15-17 years old experiencing medium to high academic stress, and used medium to high maladaptive coping strategies based on screening. Instruments used were Educational Stress Scale for Adolescents (ESSA) and Brief-COPE. The results of quantitative analysis using ANOVA showed that there was a decrease on the average academic stress score (F (2, 10) =1.04; p < ,05), a decrease on the average maladaptive coping score (F (1.34, 6.67) = 1.87; p < ,05). Meanwhile, there was no significant decrease in the average adaptive coping score (F (1.4, 7.03) =1.04; p < ,05). Qualitatively, students can understand more about academic stressors, stress reactions they experienced, and coping strategies suitable for each of them. In conclusion, this online intervention can help 2nd grade high school students lower academic stress, and decrease maladaptive coping strategies, although this does not help students to enhance adaptive coping strategies significantly.